Keberlanjutan Lembaga Wakaf: Tinjauan Literatur Sistematis tentang Inovasi, Tata Kelola, dan Manajemen Risiko - Tina Kartini; Sri Widyastuti; Darmansyah Darmansyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to systematically review the literature on the sustainability of waqf institutions by focusing on the roles of innovation, governance, and risk management. The research employs a Systematic Literature Review (SLR) approach following the PRISMA guidelines. The analysis is based on peer-reviewed journal articles indexed in Scopus over the last 10–15 years, selected through rigorous inclusion and exclusion criteria. The findings indicate that the sustainability of waqf institutions is a multidimensional construct shaped not only by financial performance but also by governance quality, institutional innovation, and risk management capacity. Innovations such as cash waqf, digital waqf, and integration with Islamic financial instruments enhance efficiency and outreach, yet simultaneously increase exposure to investment and operational risks. Effective governance characterized by accountability and transparency plays a critical role in mitigating these risks and sustaining public trust. The SLR highlights that risk management functions as a strategic mediating mechanism linking innovation and governance to long-term sustainability. This study concludes that an integrative waqf management model that combines innovation, sound governance, and systematic risk management, aligned with the principles of Maqasid al-Shariah, is essential to ensure the sustainable development of waqf institutions in the contemporary context.